Revealing the Role of Microstructure and Strain Heterogeneities in the Elastic–Plastic Transition of Glassy Polymers - Reda, Hilal; Katsamba, Panayiota; Chazirakis, Anthony; Harmandaris, Vagelis (My University, 2025)
In this work, we investigate the atomic and microstructural underpinnings of glassy polymers, focusing on the transition from elastic to plastic regimes under tensile strain and the underlying mechanisms at the atomic scale via detailed atomistic simulations. We highlight the role of local heterogeneities and their interplay in stress, strain, and density fields. Our key message is that the coupling between the microstructure (density) and strain heterogeneities is crucial for the elastic–plastic transition. Regions with increased free volume facilitate activation of vitreous segments, reorganization of polymer atoms to minimize nonbonded interactions and stress dissipation, leading to enhanced mobility and delayed strain-hardening of low-density regions.
Keywords: Deformation; Materials; Physical and chemical properties; Polymers; Stress